DIGITAL MARKETING USING AISAS MARKETING FUNNEL ON SEMAKIN PEKA PRODUCTS - Naura Nafisha Saadah; Arief Budiman; Ismail Yusuf (SEAN Institute, 2023)
The AISAS (Attection, Interests, Search and Share) marketing funnel has replaced AIDMA (Attention, Interest, Desire, Memory and Action), which was created expressly to reach the target audience by analyzing the continuing behavioral changes in the context of Internet technology improvements. In today's internet era, internet users can easily search for information or share information. This study investigated the sales of Semakin Peka products that experienced fluctuations in making product sales on digital marketing through social media instagram and tags analyzed using AISAS marketing funnel (Attention, Interest, Search, Action and Share). The research objective is to investigate digital marketing in the run business and conduct an evaluation of the digital marketing experienced by Travelxism. This research is carried out qualitatively descriptively and the object in this research is the Travelxism team that provides research information through observations and interviews. In the selection of informants, the researchers used purposive sampling techniques. The results of this study show that the concept of the AISAS model can meet the set of information and communication needed by the audience then the AISAS model occurs when attention arouses interest, customers start searching, then move to act and share.